Specificity out of clutter: A hypothetical role of G protein‐coupled receptors in the non‐genomic effect of steroids. Issue 7 (19th February 2013) - Wang, Chen; Li, Yi-Jia; Cao, Ji-Min
Abstract : The non‐genomic effect has been considered to underlie the rapid action of steroids. This signaling is initiated at the plasma membrane‐level and does not directly influence gene expression. Recent studies have provided detailed information on their downstream pathways, but less is known about the nature of correlated membrane‐bound receptors. Here, we propose that binding of steroids to a consensus motif, namely CRAC, of G protein‐coupled receptors (GPCRs) shifts the agonist‐binding state of receptors and accounts for this effect to a certain extent. The interaction between steroids and GPCRs is specific, while the identities of the GPCRs involved are not restrained, which can coordinate the high heterogeneity of this signaling and reconcile multiple discrepancies in the literature. Abstract : ► The non‐genomic effect of steroids is via a membrane‐associated signaling. ► Binding of steroids to a special sequence (namely CRAC) of GPCR accounts for this non‐genomic effect. ► This hypothesis provides a novel insight for the allosteric regulation of steroids signaling.